Effects of Reading Fluency and Comprehension Supplemental Education Program (OKA2DEP) on Reading Skills of Students with Specific Learning Disabilities - Bora Görgün; Macid, Ayhan Melekoğlu (Reading & writing quarterly, 2022)
This study aimed to develop the Reading Fluency and Comprehension Supplemental Education Program (OKA 2 DEP) and investigate the effects on reading fluency and comprehension skills of students with specific learning disabilities (SLD) in Turkey. OKA 2 DEP is the abbreviation of the Turkish name of the program and OKA stands for both reading fluency and reading comprehension and therefore had 2 as a superscript number. DEP stands for Supplemental Education Program. OKA 2 DEP contains the keyword/mnemonic, repeated reading and story map strategies, and the word cards exercises. The changing criterion design, which belongs to the single subject designs, was used for the study. Social validity data were collected through subjective evaluation and social comparison. Results showed that OKA 2 DEP was effective in developing participants' reading fluency and comprehension and that they were able to maintain these skills one, two and three months after completing the implementation. Findings indicated that participants and their parents were satisfied with the effects of OKA 2 DEP, but participating students' reading levels were still behind their peers without disabilities.